Arthroscopic Suprapectoral and Open Subpectoral Biceps Tenodesis: A Comparison of Minimum 2-Year Clinical Outcomes. (November 2014) - Werner, Brian C.; Evans, Cody L.; Holzgrefe, Russel E.; Tuman, Jeffrey M.; Hart, Joseph M.; Carson, Eric W.; Diduch, David R.; Miller, Mark D.; Brockmeier, Stephen F.
Background: While a vast body of literature exists describing biceps tenodesis techniques and evaluating the biomechanical aspects of tenodesis locations or various implants, little literature presents useful clinical outcomes to guide surgeons in their decision to perform a particular method of tenodesis. Purpose/Hypothesis: To compare the clinical outcomes of open subpectoral biceps tenodesis (OSPBT) and arthroscopic suprapectoral biceps tenodesis (ASPBT). Our null hypothesis was that both methods would yield satisfactory results with regard to shoulder and biceps function, postoperative shoulder scores, pain relief, and complications. Study Design: Cohort study; Level of evidence, 3. Methods: Patients who underwent either ASPBT or OSPBT for isolated superior labrum or long head of the biceps lesions with a minimum follow-up of 2 years were evaluated with several validated clinical outcome measures and physical examinations including range of motion and strength. Results: Between 2007 and 2011, a total of 82 patients met all inclusion and exclusion criteria, which included 32 patients with ASPBT and 50 patients with OSPBT; 27 of 32 (84.4%) patients with ASPBT and 35 of 50 (70.0%) patients with OSPBT completed clinical follow-up. Overall outcomes for both procedures were satisfactory. No significant differences were noted in postoperative Constant-Murley (ASPBT: 90.7; OSPBT: 91.8; P = .755), American Shoulder and Elbow Surgeons (ASPBT: 90.1; OSPBT: 88.4; P = .735), Single Assessment Numeric Evaluation (ASPBT: 87.4; OSPBT: 86.8; P = .901), Simple Shoulder Test (ASPBT: 10.4; OSPBT: 10.6; P = .762), long head of the biceps (ASPBT: 91.6; OSPBT: 93.6; P = .481), or Veterans RAND 36-Item Health Survey (ASPBT: 81.0; OSPBT: 80.1; P = .789) scores. No significant range of motion or strength differences was noted between the procedures. Conclusion: Both ASPBT and OSPBT yield excellent clinical and functional results for the management of isolated superior labrum or long head of the biceps lesions. No significant differences in clinical outcomes as determined by several validated outcome measures were found between the 2 tenodesis methods, nor were any significant range of motion or strength deficits noted at a minimum 2 years postoperatively.